Intention to use e-learning among UiTM lecturers / Nur Asyira Naziron, Zarinah Abu Yazid and Shahreena Daud - Naziron, Nur Asyira; Abu Yazid, Zarinah; Daud, Shahreena (2012)
Recent developments in information technologies such as e-Iearning are becoming widespread and offer significant changes to improve the delivery of learning in schools and higher institutions. This scenario requires lecturer to adapt changes in their teaching, from conventional system to e-Iearning. Due to this, a study on intention to use e-Iearning among academics at UiTM Melaka was undertaken. The purpose of this study is to investigate the effect of two independent variables (resistance to change and attitude towards e-Iearning system) on the dependent variable, intention to use e-Iearning systems. Technology Acceptance Model (TAM) is the primary basis for this study. Questionnaires were used to collect data and 110 lecturers were involved as respondents. Multiple Linear Regression (MLR) was used to analyze the effect of independent variables on lectures' intention to use e-Ieaming systems. Findings revealed that resistance to change and attitude towards e-Iearning systems are significant predictors of lecturers' intention to use e-Ieaming systems. The implications of these findings to UiTM administrators and lecturers were discussed.